2016
DOI: 10.1634/theoncologist.2016-0068
|View full text |Cite
|
Sign up to set email alerts
|

Decision Aids Can Support Cancer Clinical Trials Decisions: Results of a Randomized Trial

Abstract: Background. Cancer patients often do not make informed decisions regarding clinical trial participation. This study evaluated whether a web-based decision aid (DA) could support trial decisions compared with our cancer center's website. Methods. Adults diagnosed with cancer in the past 6 months who had not previously participated in a cancer clinical trial were eligible. Participants were randomized to view the DA or our cancer center's website (enhanced usual care [UC]). Controlling for whether participants h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 19 publications
(27 reference statements)
0
20
0
Order By: Relevance
“…These proposals include using novel communication strategies (e.g. audio or video platforms), decision-aids and question prompt lists [11,17,[40][41][42][43]. It has also been suggested that information could be given out in smaller quantities, over varied periods, and that investigators should systematically ask individuals to recall the information given when decisions are confirmed, and consent taken [36].…”
Section: Discussionmentioning
confidence: 99%
“…These proposals include using novel communication strategies (e.g. audio or video platforms), decision-aids and question prompt lists [11,17,[40][41][42][43]. It has also been suggested that information could be given out in smaller quantities, over varied periods, and that investigators should systematically ask individuals to recall the information given when decisions are confirmed, and consent taken [36].…”
Section: Discussionmentioning
confidence: 99%
“…Of the small number of DAs that aim to improve decisionmaking for trial participation (rather than aiming to improve the presentation of information or mode of delivery) most focus on specific oncology trials [23]. These DAs show some potential promise in improving key decision outcomes such as knowledge, values clarification, and decision conflict, while not negatively impacting recruitment or intention to participate [20,21,24]. A recent systematic review of decision aids for trials only identified one study that evaluated the effectiveness of decision aids compared to standard information in the informed consent process for clinical trials [16].…”
Section: Methodsmentioning
confidence: 99%
“…It will include preference-clarifying components to assist users in their decision-making, and invitation of other members of one's family to help with difficult decisions and clarifications. A recent randomized control trial showed that a web-based decision aid performed better than a website in preparing patients for decision about clinical trial participation (Politi et al 2016).…”
Section: Proposed Solutionmentioning
confidence: 99%